2010
DOI: 10.1017/s1755267210001065
|View full text |Cite
|
Sign up to set email alerts
|

Inventory of benthic amphipods from fine sand community of the Iberian Peninsula east coast (Spain), western Mediterranean, with new records

Abstract: Inventory of benthic amphipods from fine sand community of the Iberian Peninsula east coast (Spain) (2004 -2008) of the shallow (12-20 m) soft-bottom homogeneous fine-sand community have allowed the collection of 55 marine amphipod species (53 Gammaridea and 2 Caprellidea) along the 250 km of Iberian Peninsula east coast (Spain, Mediterranean Sea). Among the species recorded, one recently described is new to science, five were collected for the first time in the Spanish Mediterranean and 14 were recorded for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
1
16
0
1
Order By: Relevance
“…However, only one species, Ampelisca brevicornis (Costa, 1853), can be considered cosmopolitan. The percentage of Mediterranean endemism (20.6%) was similar to that obtained in previous amphipod studies in the Strait of Gibraltar area (Conradi andLópez-Gónzalez 1999, Guerra-García et al 2009), but surprisingly higher than that obtained on the east coast of the Iberian Peninsula (12.7%) (de-la-Ossa-Carretero et al 2010). …”
Section: Biogeographical Considerationssupporting
confidence: 89%
See 1 more Smart Citation
“…However, only one species, Ampelisca brevicornis (Costa, 1853), can be considered cosmopolitan. The percentage of Mediterranean endemism (20.6%) was similar to that obtained in previous amphipod studies in the Strait of Gibraltar area (Conradi andLópez-Gónzalez 1999, Guerra-García et al 2009), but surprisingly higher than that obtained on the east coast of the Iberian Peninsula (12.7%) (de-la-Ossa-Carretero et al 2010). …”
Section: Biogeographical Considerationssupporting
confidence: 89%
“…Studies carried out in the Atlantic zone of the Iberian Peninsula found between 34 and 79 different amphipod species in the northwestern area (Cunha et al 1999, Lourido et al 2008, Cacabelos et al 2010 and 93 species on the southern Portuguese coast (Carvalho et al 2012). On the other hand, in the Mediterranean area, an inventory of soft-bottom amphipods from the east coast of the Iberian Peninsula revealed the presence of 55 different species (de-la-Ossa-Carretero et al 2010). This value is slightly higher than that found in the present work.…”
Section: Biogeographical Considerationsmentioning
confidence: 99%
“…In order to investigate available information about the presence of Microdeutopus sporadhi in the Mediterranean Sea, a check was performed on: -the checklists available for different geographical areas of the Mediterranean Sea, in particular for the coasts of Italy (Ruffo, 2010), France (Dauvin & BellanSantini, 2002), Spain (García & Jaume, 1997De-la-Ossa-Carretero et al, 2010), Algeria (Bakalem & Dauvin, 1995;Grimes et al, 2009), Tunisia (ZakhamaSraieb et al, 2009, Libya (Ortiz & Petrescu, 2007), Israel (see Sorbe et al, 2002), Turkey (Gözcelioğlu, 2002;Bakir & Çevirgen, 2010), Greece (Stefanidou & Voultsiadou-Koukoura, 1995;Koukouras, 2010), Rovinj (Croatia) and adjacent regions (Krapp-Schickel & Zavodnik, 1993-1996, besides the Sea of Marmara (Bakir, 2012), the Bosphorus (Balkis et al, 2002), and the Black Sea (Sezgin & Katağan, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…It had previously only been reported thrice inside the Lusitanian region; twice from coastal waters of Portugal (Bellan-Santini and Marques 1986; Marques and Bellan-Santini 1987) and once from southeast of the Bay of Biscay, Spain (Martínez et al 2007). The species was not found in the Azores archipelago (Portugal), located in the middle north Atlantic region (Rosa Lopes et al 1993) nor in the eastern side of the Iberian Peninsula, western Mediterranean (Conradi and López-González 1999;de-la-Ossa-Carretero et al 2010, 2016. Also the species was not reported from the Portuguese continental shelf during a comprehensive sampling of the soft-bottom macrofauna (Martins et al 2013).…”
Section: Discussionmentioning
confidence: 96%